Is the Growth Momentum in Latin America Sustainable? - Sosa, Sebastian (IMF Working Papers; Working Paper ;, 2013)
A favorable external environment coupled with prudent policies fostered output growth in most of Latin America during the last decade. But, what were the drivers of this strong growth performance from the supply side and will this momentum be sustainable in the years ahead? We address these questions by identifying the proximate causes of the recent high GDP growth and estimating potential growth rates for the period ahead for a large group of Latin American countries based on standard (Solow-style) growth accounting methodologies. We find that factor accumulation (especially labor), rather than growth in total factor productivity (TFP), remains the main driver of GDP growth. Moving forward, given the expected moderation of capital accumulation and some natural constraints on labor, the strong growth momentum is unlikely to be sustainable unless TFP performance improves significantly.